2023
DOI: 10.3390/healthcare11222934
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution and Associated Factors of Adherence to Mammography Screening among Women in Spain: Results from Two National Health Surveys (2017–2020)

Silvia Portero de la Cruz,
Luis M. Béjar,
Jesús Cebrino

Abstract: Ensuring equity in cancer screening is recommended by the European Commission. Despite the fact that breast cancer screening is a free population-based program in Spain, there remains considerable variation in the adherence to screening rate among population groups. This study was designed to describe the adherence of breast cancer screening in women in Spain, to evaluate the evolution in the period from 2017 to 2020, and to determine the variables that influence choosing to undergo breast cancer screening. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This study analysed the cancers detected in women who participated in the VR-BCSP. Some studies have observed that women participating in screening programs tend to have healthier behaviours [ 41 , 42 ]. On the other hand, other studies have shown that BC most frequently diagnosed in screening are HR+ [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study analysed the cancers detected in women who participated in the VR-BCSP. Some studies have observed that women participating in screening programs tend to have healthier behaviours [ 41 , 42 ]. On the other hand, other studies have shown that BC most frequently diagnosed in screening are HR+ [ 39 ].…”
Section: Discussionmentioning
confidence: 99%